Geological, Geographical and Legal Considerations for the Conservation of Unique Iron Oxide and Sulphur Flows at el Laco and Lastarria Volcanic Complexes, Central Andes, Northern Chile - Henriquez-Barrientos, F (Springer Verlag, 2011)
Considering the exceptional geological characteristics of iron oxide and sulphur lavas structures cropping out at El Laco and Lastarria volcanic complexes in Northern Chile, their geographical context, and the Chilean legal framework for conservation, the authors make a general assessment of the geological heritage value of both volcanoes, while analysing the possibilities and challenges that arise in order to protect them. Relevant issues in this matter are the lack of appropriate laws and of applied geoconservation experience in the country, and the difficulty of attracting financial resources but also a big potential for conciliating conservation with mining, different alternatives of tourism—including geotourism—, or other sustainable initiatives, in a naturally and culturally diverse and rich region, already known as a world class tourist destination. Thus results the need to identify the relevant geosites present in each volcano, to emphasize their study and knowledge, as well as a proactive role of public authorities in order to effectively protect these extremely rare and vulnerable geological features. Analysing the specific cases of both volcanic complexes as possible geological heritage locations, the authors aim to highlight the main problems that need to be solved in order to introduce proper geoconservation in the area. © Springer-Verlag 2011.